Analysis of the molecular basis of Saccharomyces cerevisiae mutant with high nucleic acid content by comparative transcriptomics. (April 2021) - Guo, Xuewu; Zhao, Bin; Zhou, Xinran; Lu, Dongxia; Wang, Yaping; Chen, Yefu; Xiao, Dongguang
Graphical abstract: Highlights: A mutant with high-nucleic acid content was screened by using chemical mutagenesis. The expression of HXT1 gene was up-regulated in the mutant. The expression of GSP2 gene and CTT1 gene was down-regulated in the mutant. The molecular mechanism of enhanced RNA synthesis was revealed. Abstract: Ribonucleic acid (RNA) and its degradation products are important functional components widely used in the food industry. Transcription analysis was used to explore the genetic mechanism underlying nucleic acid synthesis in the chemical mutant Saccharomyces cerevisiae strain BY23-195 with high nucleic acid content. Results showed that ribosome biogenesis, meiosis, RNA transport, mitogen-activated protein kinase (MAPK) signaling pathway, tryptophan metabolism, carbon metabolism, and longevity regulating pathway are closely related to the high nucleic acid metabolism of S. cerevisiae . Fourteen most promising genes were selected to evaluate the effect of single-gene deletion or overexpression on the RNA synthesis of S. cerevisiae . Compared with the RNA content of the parent strain BY23, that of mutant strains BY23-HXT1, BY23-ΔGSP2 and BY23-ΔCTT1 increased by 8.19%, 11.60% and 14.00%, respectively. The possible reason why HXT1, GSP2, and CTT1 affect RNA content is by regulating cell fitness. This work was the first to report that regulating the transcription of HXT1, GSP2, and CTT1 could increase the RNA content of S. cerevisiae. This work also provides valuable knowledge on the genetic mechanism of high nucleic acid synthesis in S. cerevisiae and new strategies for increasing its RNA content .